Sociological conceptualizations of compassion fatigue: Expanding our understanding. Issue 2 (8th December 2020) - Vaccaro, Christian; Swauger, Melissa; Morrison, Shayna; Heckert, Alex
Abstract: Compassion fatigue has been primarily studied at the micro level and framed as a psychological "personal trouble" that results from one's personality traits, demographic characteristics, or life and work stressors. In addition, compassion fatigue is used to predict other psychological outcomes such as burnout, depersonalization, and stress. This literature on compassion fatigue has been reviewed, in order to illustrate areas where sociologists can contribute to a more nuanced understanding of the phenomenon. In this article we conceptualize compassion fatigue as a sociological concept and overview the potential ways that sociological approaches can enhance our understanding. We draw on the literatures of emotion work, social exchange theory, and macrolevel sociological theories to facilitate the use of compassion fatigue from a sociological perspective. For example, we use concepts such as social integration and anomie to stimulate thinking about rates of compassion fatigue.